Efektivitas Model Pembelajaran Kooperatif Reciprocal Teaching (RT) dan Namber Heads Together (NHT) Untuk Meningkatkan Hasil Belajar Ekonomi - Sunarti Djoko; Frans Cembus Bosso (Jurnal Ilmiah Wahana Pendidikan, 2022)
Learning outcomes are influenced by two factors, namely internal factors and external factors. Factors discussed in this study are external factors, namely learning methods. In this study, the learning method used is the Reciprocal Teaching (RT) model and the Numbered Haed Togther (NHT) learning model. The problem in this study is whether there is a difference in learning outcomes for the Reciprocal Teaching (RT) model and the learning outcomes for Numbered Haed Togther (NHT) economics subjects in the labor material of class XI IPS students at SMA Negeri 2 West Halmahera. The population in this study were students of class XI IPS at SMA Negeri 2 Halmahera Barat in 2021. From the population, 2 classes were taken as samples, namely class XI IPS 1 and XI IPS 2 as the control class. In the experimental class, the Reciprocal Teaching (RT) learning model was applied, while in the control class the Numbered Haed Togther (NHT) learning model was used. Data collection methods in this study were observation, learning outcomes tests and documentation. Before using the research instrument, the test items were first tested for the level of validity, reliability, degree of difficulty of the items and the distinguishing power of items. The results showed that students who were taught using the Reciprocal Teaching (RT) learning model had a better level of effectiveness compared to students who were taught using the Numbered Haed Togther (NHT) learning model. This is shown by the average score of students in the experimental class (XI IPS 1 taught by using the Reciprocal Teaching (RT) learning model, which is 80.91 better than students in the control class (XI IPS 2 taught using the Numbered Haed Togther model). (NHT)) with an average score of 76.14. Likewise with classical learning outcomes. Students who are taught using the Reciprocal Teaching (RT) learning model classical completeness reaches 95.45%, while in the control class taught by the Numbered learning model Haed Togther (NHT) has 82.61% classical completeness.Based on the results of this study, it can be concluded that there is a difference in the learning outcomes of the experimental class (Reciprocal Teaching (RT)) and the learning outcomes of the control class (Numbered Haed Togther (NHT)).